Sensitivity improvement of kukoamine determination by complexation with dihydrogen phosphate anions in capillary zone electrophoresis. Issue 15 (30th June 2015) - Li, Yuan‐Yuan; Di, Rui; Hsu, Wing‐Leung; Huang, Ye‐Qing; Sun, Hongyan; Cheung, Hon‐Yeung
Abstract : A novel complexation between kukoamines and dihydrogen phosphate ions (DPI) during CZE was discovered to improve the UV signal of kukoamine by around 30‐fold. This complexation formed by electric current was attributed to the hydrogen bonding of hydroxyl and amino (or amide) groups between the analyte and electrolyte anions. The established CZE method is low‐cost, easy to operate, and eco‐friendly, and it was shown to be superior to HPLC in terms of separation capability, efficiency, specificity, and sensitivity. We believe that our CZE method can be applied as an alternative to HPLC for kukoamine assay. The approach described here can be also extended for analyzing other compounds with similar functional groups.